Trial Protocol: Communicating DNA-based risk assessments for Crohn's disease: a randomised controlled trial assessing impact upon stopping smoking - Whitwell, Sophia CL (BioMed Central, 2011)
BACKGROUND: Estimates of the risk of developing Crohn's disease (CD) can be made using DNA testing for mutations in the NOD2 (CARD15) gene, family history, and smoking status. Smoking doubles the risk of CD, a risk that is reduced by stopping. CD therefore serves as a timely and novel paradigm within which to assess the utility of predictive genetic testing to motivate behaviour change to reduce the risk of disease. The aim of the study is to describe the impact upon stopping smoking of communicating a risk of developing CD that incorporates DNA analysis. We will test the following main hypothesis: Smokers who are first degree relatives (FDRs) of CD probands are more likely to make smoking cessation attempts following communication of risk estimates of developing CD that incorporate DNA analysis, compared with an equivalent communication that does not incorporate DNA analysis. METHODS/DESIGN: A parallel groups randomised controlled trial in which smokers who are FDRs of probands with CD are randomly allocated in families to undergo one of two types of assessment of risk for developing CD based on either: i. DNA analysis, family history of CD and smoking status, or ii. Family history of CD and smoking status The primary outcome is stopping smoking for 24 hours or longer in the six months following provision of risk information. The secondary outcomes are seven-day smoking abstinence at one week and six month follow-ups. Randomisation of 470 smoking FDRs of CD probands, with 400 followed up (85%), provides 80% power to detect a difference in the primary outcome of 14% between randomised arms, at the 5% significance level. DISCUSSION: This trial provides one of the strongest tests to date of the impact of communicating DNA-based risk assessment on risk-reducing behaviour change. Specific issues regarding the choice of trial design are discussed. TRIAL REGISTRATION: ISRCTN: ISRCTN21633644